2008
DOI: 10.1093/glycob/cwn077
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans N-glycans containing a Gal-Fuc disaccharide unit linked to the innermost GlcNAc residue are recognized by C. elegans galectin LEC-6

Abstract: We report a detailed structural analysis of the N-glycans of Caenorhabditis elegans recognized by C. elegans galectin LEC-6. Glycoproteins of C. elegans captured by an immobilized LEC-6 affinity adsorbent were isolated. The N-glycans of these glycoproteins were then liberated by hydrazinolysis and labeled with the fluorophore 2-aminopyridine (PA). The derived pyridylaminated (PA)-sugars were further fractionated by rechromatography on immobilized LEC-6 adsorbent and by reversed-phase high-performance liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…[16][17][18][19][20][21] Recently, we found that another C. elegans galectin LEC-6 strongly interacts with N-glycans containing a Gal-Fuc disaccharide unit attached at position 6 of the innermost GlcNAc residue. 22) We also found that LEC-6 interacts with Galb1→4Fuc more strongly than does Galb1→ 3Fuc 23) by using chemically synthesized Galb1→4Fuc and Galb1→3Fuc. 24) Furthermore, the tandem repeat-type nematode galectin LEC-1 also shows preferential binding to Galb1→4Fuc.…”
Section: )mentioning
confidence: 51%
“…[16][17][18][19][20][21] Recently, we found that another C. elegans galectin LEC-6 strongly interacts with N-glycans containing a Gal-Fuc disaccharide unit attached at position 6 of the innermost GlcNAc residue. 22) We also found that LEC-6 interacts with Galb1→4Fuc more strongly than does Galb1→ 3Fuc 23) by using chemically synthesized Galb1→4Fuc and Galb1→3Fuc. 24) Furthermore, the tandem repeat-type nematode galectin LEC-1 also shows preferential binding to Galb1→4Fuc.…”
Section: )mentioning
confidence: 51%
“…We found that LEC-6 interacts strongly with N-glycans containing a Gal-Fuc disaccharide unit attached to position 6 of the innermost GlcNAc residue. 16) In order to identify the linkage between the galactose and fucose residues, and examine the structure of the endogenous glycoepitope recognized by LEC-6, we compared the binding strengths of the chemically synthesized Galb1-4Fuc and Galb1-3Fuc, 17) and found that LEC-6 interacts more strongly with Galb1-4Fuc than with Galb1-3Fuc.…”
Section: -15)mentioning
confidence: 99%
“…Two pyridylaminated-LEC-6-binding glycans, D3 and E3, 16) were subjected to FAC analysis by using LEC-1-, LEC-1Nh-, and LEC-1Ch-immobilized columns (results are shown in Fig. 2).…”
Section: Of Ref 18)mentioning
confidence: 99%
See 1 more Smart Citation
“…To search for it, Takeuchi et al isolated N-type glycoproteins bound by C. elegans galectin LEC-6. 15) Matrix assisted laser desorption/ionization-time of flight (MALDI-TOF)/TOF analysis in conjunction with glycosidase digestion elucidated that the glycoproteins contain a Gal-Fuc disaccharide unit attached to the innermost GlcNAc (N-acetylglucosamine) residue. Among several Gal-Fuc units, in which D-galactose and L-fucose are differentially linked at some positions, we assumed that Galb1-4Fuc should be the endogenous glyco-epitope because its presence had been confirmed in C. elegans N-glycans.…”
mentioning
confidence: 99%